2006
DOI: 10.1111/j.1399-0004.2005.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HFE C282Y and H63D in Jewish populations and clinical implications of H63D homozygosity

Abstract: The frequencies of C282Y and H63D mutations of the HFE gene vary between different populations. A previous study showed an unexpectedly high H63D frequency in Chuetas (a population of Jewish descent). The present study addressed the question of the distribution of these mutations in Jewish populations from different origins and studied the possible causes of the high H63D frequency in Chuetas. Moreover, to improve the understanding of the controversial relationship between H63D homozygosity and iron overload, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…These data suggest that HH is a rare metabolic disorder in this community. Interestingly, the H63D allele frequency present in 17.1% of the chromosomes (95% CI 13.2-21) was similar to data reported from the Southern Europe (13.6-20.4%) (8) and Sephardic Jewish (13.3%) (9) populations. Given that one in 34 paisa subjects is predicted to be homozygous for the H63D mutation and H63D homozygous status could be a pre-disposing factor for other diseases, further population screening is warranted to evaluate the real clinical significance of this allele in the paisa population.…”
supporting
confidence: 86%
“…These data suggest that HH is a rare metabolic disorder in this community. Interestingly, the H63D allele frequency present in 17.1% of the chromosomes (95% CI 13.2-21) was similar to data reported from the Southern Europe (13.6-20.4%) (8) and Sephardic Jewish (13.3%) (9) populations. Given that one in 34 paisa subjects is predicted to be homozygous for the H63D mutation and H63D homozygous status could be a pre-disposing factor for other diseases, further population screening is warranted to evaluate the real clinical significance of this allele in the paisa population.…”
supporting
confidence: 86%
“…Even when combined with data reported by Matas et al, 7 the allele frequency of 0.24% in both groups is in the rare range ( Table 1). The Yemenite group investigated here for the first time exhibited an allele frequency of 0%.…”
Section: Discussionsupporting
confidence: 50%
“…12,22 Although C282Y homozygosity confers the highest risk for iron overload, H63D mutation (in homozygosity or compound heterozygosity) was also associated with increased risk. 7,[23][24][25][26][27] Furthermore, aggravation of iron overload may occur when additional nongenetic or genetic modifier such as ␤-thalassemia trait is coinherited. [27][28][29][30][31][32] The frequency of ␤-thalassemia trait among Oriental Jews originating from Kurdistan is high, with carrier frequency estimated at 20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study in mice showed that homozygosity for the orthologous of the H63D mutation also increased iron levels (19). The H63D homozygosity genotype has been associated with an iron overload genotype (12, 24–26). For 80%, this genotype is clinically undetectable; however, 20% do develop biochemical evidence of iron overload which is approximately twice the rate found in HFE wild type subjects.…”
Section: Discussionmentioning
confidence: 99%